Exploring the Compton Scattering Phenomenon with Virtual Learning Under Project Based Learning Model (PjBL) - Ahmad Swandi; Sri Rahmadhanningsih; Irfan Yusuf; Sri Wahyu Widyaningsih (Kasuari: Physics Education Journal (KPEJ), 2021)
In physics learning, some concepts cannot be explored through experimentation and direct observation, especially abstract concepts. One of the efforts made to overcome this problem is to use interactive visualization through the Project Based Learning model. This study aims to examine the effect of using visualization / virtual media on the Compton Scattering phenomenon through Project Based Learning on students' conceptual understanding. This research is a quasi-experimental study using a non-equivalent pretest-posttest control group design pattern. The research instrument uses a concept understanding test that has been validated by experts. Hypothesis testing using the t-polled variant test. Improved understanding of the concept is determined based on the results of the N-gain test. The results showed an increase in students' understanding of concepts in both classes. The experimental class experienced a higher understanding of the concept than the control class with N-Gain 55.79% and 12.84%, respectively. Therefore, there is a positive and significant influence on the use of virtual media with the PjBL model on Compton's Scattering material.